Variabilidade genética populacional em variedades botânicas de Hancornia speciosa Gomes (Apocynaceae): estratégias para conservação no cerrado - Rodrigues, Eduardo Borges (2015)
Due to constant degradation, populations of plants in the Cerrado may be losing genetic variability, thereby them to stay in their natural habitat may be compromised. Aiming to generate useful genetic information for the implementation of conservation programs in situ and ex situ to Hancornia speciosa Gomes (mangabeira), this study aimed to evaluate the genetic structure of populations in H. speciosa occurring in the Cerrado, contributing to the knowledge genetic and spatial patterns related to geographic distribution and genetic differentiation between botanical varieties. In the first chapter it evaluated the magnitude of genetic diversity levels four botanical varieties of the species, and also the genetic divergence between them. As a result, it was observed that there is a high genetic diversity (He = 0.636), the assessed loci. The average values of genetic diversity observed heterozygosity, inbreeding coefficient intrapopulation and allelic richness were not significant, showing that there is no difference of these genetic parameters compared the botanical varieties of H. speciosa. And despite the variation between varieties to be significant (FCT = 0.027; p = 0.017) greater differentiation is between populations within varieties (FSC = 0.104; p <0.001) and in independent populations of varieties (FST = 0.131; p <0.001). The variety H. speciosa var. speciosa presents with the botanical variety genetically most divergent, then the variety H. speciosa var. cuyabensis. Phenotypic plasticity may be contributing to differentiate between botanical varieties. In the second chapter, the genetic variability within and among populations of H. speciosa throughout the Brazilian Cerrado was evaluated and, if there is spatial pattern of genetic variability on a regional scale, along the geographical distribution of the species. As a result, it was observed that populations have high genetic variability and significant inbreeding (f = 0.103) due crosses between unrelated individuals. The genetic differentiation between populations was moderate to high, but significant (θ = 0.126; RST = 0.253). The differentiation of populations occurred as a result of isolation by distance. Populations with distance up to 280m were more similar than expected by chance. There were significant signs of genetic bottleneck for some natural populations of mangabeira. In the third chapter, it was shown as conservation planning procedures can be used to establish optimal strategies of conservation in situ and ex situ of a single species, using H. speciosa, a species widely distributed in the Brazilian Cerrado, as a case study. Nine populations were selected as priorities for conservation in situ and another seven were considered ideals in addition to the genetic variability of the germplasm collection of the Universidade Federal de Goiás.